GRAMMAR IN LINGUISTICS (Лучшие интеллектуальные исследования, 2025)
ABSTRACT. This article provides a brief summary of the grammar is a central component of linguistics, the scientific study of language. It encompasses the set of structural rules that govern the composition of clauses, phrases, and words in any given natural language. Grammar is not just a list of rules for speaking or writing correctly, but a system that reflects how languages function and evolve.